The Effect Of Work Value And Work Discipline On Employee Performance With Leadership Style As A Moderating Variable - Riri Yamelda, Almasdi (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2024)
This study aims to find out and estimate: the influence of work value and work disciplineon employee performance with leadership style as a moderating variable in the Regional Finance and Assets Agency of Agam Regency. This type of research is quantitative, descriptive, associative. The population of this study is all employees of the Agam Regency Regional Finance and Assets Agency, totaling 52 employees. Sample withdrawal was carried out by means of saturated sampling of 52 people. Data were collected with a Likert scale model questionnaire. The data analysis technique is Smart PLS version 3. The results of the study are: (1) Work value has a positive and significant effect on employee performance. (2) Work discipline has a positive and significant effect on employee performance. (3) Leadership style has a positive and significant effect on employee performance. (4) The leadership style of moderating work value has a positive and insignificant effect on employee performance. (5) The leadership style of moderating work discipline has a positive and insignificant effect on employee performance.